2019
DOI: 10.1111/1755-0998.12950
|View full text |Cite
|
Sign up to set email alerts
|

Making use of the social network in conservation genomics: Integrating kinship and network analyses to understand connectivity

Abstract: Inferring and quantifying recent barriers to connectivity is increasingly important for conservation and management in a world undergoing rapid environmental change. Traditional measures of genetic differentiation can take many generations to reflect a new barrier to connectivity. Although methods that use the linkage disequilibrium signal in mixed genetic samples are able to reflect recent levels of gene flow, they are not suitable for use in situations with low levels of genetic differentiation. Kinship‐base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Recent advances have been made to infer the probable location of parents based on the location of full‐sibling pairs, but such pairs can be rare in many data sets (Kormann et al, 2012). Others have used extended kin pairs as qualitative evidence of connectivity, or to detect the presence of low‐permeability barriers (Escoda et al, 2017), but do not explicitly quantify levels of dispersal (Carroll & Gaggiotti, 2019; Vandergast et al, 2019). Here, we have shown that it is possible to use both close and distant kin relations to generate quantitative estimates of dispersal rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent advances have been made to infer the probable location of parents based on the location of full‐sibling pairs, but such pairs can be rare in many data sets (Kormann et al, 2012). Others have used extended kin pairs as qualitative evidence of connectivity, or to detect the presence of low‐permeability barriers (Escoda et al, 2017), but do not explicitly quantify levels of dispersal (Carroll & Gaggiotti, 2019; Vandergast et al, 2019). Here, we have shown that it is possible to use both close and distant kin relations to generate quantitative estimates of dispersal rates.…”
Section: Discussionmentioning
confidence: 99%
“…used extended kin pairs as qualitative evidence of connectivity, or to detect the presence of low-permeability barriers (Escoda et al, 2017), but do not explicitly quantify levels of dispersal (Carroll & Gaggiotti, 2019;Vandergast et al, 2019). Here, we have shown that it is possible to use both close and distant kin relations to generate quantitative estimates of dispersal rates.…”
Section: Estimating Contemporary Dispersal Using Pedigreesmentioning
confidence: 97%